1993
DOI: 10.1210/en.132.1.337
|View full text |Cite
|
Sign up to set email alerts
|

Cellular events involved in hormonal control of receptor-mediated endocytosis: regulation occurs at multiple sites in the low density lipoprotein pathway, including steps beyond the receptor

Abstract: We used biochemical and quantitative structural approaches to analyze hormonal regulation of receptor-mediated endocytosis of human low density lipoprotein (LDL) by differentiating rat granulosa cells in culture. We studied uptake and metabolism of 125I-labeled LDL and distribution of gold-labeled LDL in nontreated and FSH- or FSH/androstenedione-treated granulosa cells. FSH and androstenedione worked together to enlarge the segment of the granulosa cell population capable of accumulating LDL and to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…One mechanism by which gonadotropins stimulate the production of sex hormones is by their effect on apolipoprotein receptors and postreceptor cellular function. In differentiating rat granulosa cells in culture, FSH caused an increase in the number of LDL receptors on the cell membrane, an increase in the rate of uptake of LDL, and a decrease in the time for LDL to reach lysosomes ( 16).…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism by which gonadotropins stimulate the production of sex hormones is by their effect on apolipoprotein receptors and postreceptor cellular function. In differentiating rat granulosa cells in culture, FSH caused an increase in the number of LDL receptors on the cell membrane, an increase in the rate of uptake of LDL, and a decrease in the time for LDL to reach lysosomes ( 16).…”
Section: Discussionmentioning
confidence: 99%
“…However, in FSH- or FSH plus androstenedione-treated granulosa cells the rate of LDL receptor absorption increases while the time needed for the LDL to reach the lysosome decreases compared to non-hormone-treated cells suggesting this pathway is used for steroidogenesis [25]. As endosomes contain a large percentage of the cytosolic cholesterol present in the cell; they can function in the trafficking of intracellular cholesterol to the mitochondria without first absorbing cholesterol from the plasma membrane.…”
Section: Plasma Membranementioning
confidence: 99%
“…Maturing follicles are in close contact with peripheral blood, suggesting granulosa cells come in contact with circulating HCV, which could lead to attachment of HCV to LDL receptors ≥ induction of apoptosis mechanism. A lower level of apoptosis in granulosa cells is associated with better outcomes for human oocytes with a higher embryo quality; with a greater correlation of pregnancy rates with lower rates of apoptosis [17,18] . In a study of 6 HCV In women higher granulosa cell apoptosis was reported as compared to controls [18] .…”
Section: Introductionmentioning
confidence: 99%